A SHORT JOURNEY TO EXPLORE THE EAST: ELTIO ALEGONDAS FORSTEN - Mulyasari, Prima Nurahmi (History Department, Semarang State University and Historian Society of Indonesia, 2015)
Tropical area is widely concerned for its biodiversity. In the past, European expansion made it possible for naturalists to explore around the world since most countries in equatorial regions were European colonies. Through the projects of natural history European imperialism tried to exploit the nature for their interests. In 1820 the Dutch government launched the establishment of Natuurkundige Kommisie voor Netherlands Indië (Natural Science Commission for Netherlands Indies). Among the few members of Natuurkundige Kommisie for Netherlands Indies was E.A Forsten who conducted his scientific research in North Celebes and Moluccan Islands in early 19th century. By mostly using Forsten’s diary and letters as the main sources this article attempts to narrate Forsten’s scientific expedition and its contribution to the natural science.Keywords: Biodiversity, E.A Forsten, natural history Wilayah tropis terkenal akan keanekaragaman hayati yang melimpah. Pada era kolonialisme, ekspansi Eropa memungkinkan bagi para naturalis Barat untuk menjelajahi kawasan equator mengingat sebagian besar negara di wilayah khatulistiwa merupakan jajahan negara-negara Eropa. Melalui proyek-proyek mempelajari alam dan penduduk di koloni-koloninya imperialisme Eropa mendanai riset terutama bagi kepentingan mereka. Pada tahun 1820 pemerintah Belanda membentuk Natuurkundige Kommisie voor Netherlands Indië (Komisi Ilmu Pengetahuan Alam untuk Hindia Belanda). Di antara beberapa anggota Natuurkundige Kommisie ialah EA Forsten yang melakukan penelitian ilmiah di Sulawesi Utara dan Kepulauan Maluku pada awal abad ke-19. Dengan sebagian besar menggunakan buku harian dan surat-surat Forsten sebagai sumber utama, artikel ini mencoba untuk menarasikan ekspedisi ilmiah Forsten beserta kontribusinya terhadap ilmu pengetahuan.Kata kunci: keanekaragaman hayati, E.A. Forsten, sejarah alam